Analisis Tantangan dan Peluang Bank Syariah dalam Mengadopsi Teknologi Digital: Studi Kasus Bank Syariah Indonesia (BSI) Tamalanrea 2 - Sayyid Haiqal Akbar; Indo Tang; Aliah Reski Yanti (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This article discusses the challenges and opportunities faced by Bank Syariah Indonesia (BSI) Tamalanrea 2 in adopting digital technology. Along with rapid technological developments, the sharia banking industry is faced with demands to innovate to increase efficiency and competitiveness. This research uses a case study approach by analyzing the digital technology adoption process carried out by BSI Tamalanrea 2. The findings show that the main challenges faced include limited human resources skilled in technology, resistance to change from some parties, as well as infrastructure problems that do not fully support. however, big opportunities also arise from ease of access for customers, faster and more transparent service improvements, and the potential for market expansion through digital platforms. This article provides recommendations for BSI and other sharia banks to strengthen technological competence, improve training for staff, and collaborate with various parties in order to maximize the potential of digital technology